Effectiveness of a brief form of group dialectical behavior therapy for binge‐eating disorder: Case series in a routine clinical setting. Issue 4 (18th January 2021) - Adams, Gillian; Turner, Hannah; Hoskins, Jessica; Robinson, Alice; Waller, Glenn
Abstract: Objective: While there is evidence to support the use of group dialectical behavior therapy (DBT) in the treatment of binge‐eating disorder (BED), treatment is relatively long compared with other evidence‐based treatments. This study explored the effectiveness of brief DBT groups for BED, delivered in a routine community setting. Method: Eighty‐four adults with BED entered 10‐week DBT group treatment in a community eating disorders service. In total, 12 groups were conducted. Patients completed measures of eating disorder pathology, anxiety, depression, and emotional eating at the start and end of treatment, and at 1‐month follow‐up. Frequency of weekly binges was recorded. Results: Outcomes were similar to those of longer versions of DBT, with an attrition rate of 26%, and significant reductions in eating disorder psychopathology and emotional eating by the end of treatment and at follow‐up. Over 50% of patients were abstinent from binge eating by Session 4. Discussion: Group DBT delivered in a 10‐session format is clinically equivalent to longer versions of the same treatment. Future research is required to explore patterns of change and to demonstrate replicability under controlled conditions, but these findings are promising for the efficient delivery of effective treatment and reducing waiting times.